BUDAYA LITERASI SISWA SEBAGAI PENDIDIKAN KARAKTER ISLAMI DI MI AL KHOIRIYYAH 2 SEMARANG - Ikramina, Mahreshaibati Bilqis (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to describe and analyze students' literacy culture in MI Al Khoiriyyah 2 Semarang. This research used descriptive qualitative research method with case study approach. The research subjects were teachers and students of MI al khoiriyyah 2 Semarang. Data collection techniques were interviews, observation, and documentation. The results of this study indicate that the literacy program at MI Al Khoiriyyah 2 Semarang, which consists of Reading Corner activities and making Mini Book, has been implemented well. Through this program, students can not only improve their literacy skills, but also can understand and take Islamic values contained in every story they read. These values are expected to shape students' character and can be applied in their daily lives, both at school and at home. The success of this program is also supported by the active participation of students and the full support of teachers and school authorities, who consistently monitor and develop literacy activities at school.